Answer:
[tex]c = -6[/tex]
[tex]d = -1[/tex]
Step-by-step explanation:
Given
See attachment for grid
Required
Find c and d
From the attachment, we have:
[tex]a = (3,5)[/tex] --- Point on A
[tex]a' = (-3,-6)[/tex] --- Corresponding point on B
When A is reflected across the x-axis, the rule is:
[tex](x,y) \to (x,-y)[/tex]
So, we have:
[tex](3,5) \to (3,-5)[/tex]
Next, is to calculate the translation from [tex](3,-5)[/tex] to [tex](-3,-6)[/tex]
This is calculated using:
[tex]3 + c = -3[/tex]
and
[tex]-5 + d = -6[/tex]
So, we have:
[tex]3 + c = -3[/tex]
[tex]c = -3-3[/tex]
---- i.e. Shift by 6 units to the left
[tex]-5 + d = -6[/tex]
[tex]d = 5 - 6[/tex]
[tex]d = -1[/tex] --- i.e. Shift by 1 unit down